Fra Sheffield til Silicon Valley. En oversigt over industrielle klyngedannelsesteorier - Madsen, Torben (Historisk Tidsskrift, 2013)
From Sheffield to Silicon Valley - an introduction to theories of industrial agglomeration Industrial agglomeration, or the concentration of particular industries in confined spaces, has gradually gained importance within the last 10-20 years, both as an academic field of research and as a topic of political interest. In Denmark, however, the political awareness and interest have far surpassed the scholarly treatment. The article at hand attempts to shift this balance by introducing and discussing some of the fundamental theories about the phenomenon. The idea that benefits derive from industrial enterprises being located in close proximity to each other, originates from the economist Alfred Marshall’s pioneering theory about "industrial districts", developed in the late 19th and early 20th century. In contrast to most of his contemporary colleagues, Marshall dismissed important parts of the orthodoxy of Adam Smith and acknowledged the presence of economic benefits caused by factors external to firms and common to the region as a whole, originating from and depending upon the distinct historical and socio-economic development of the particular areas. With the emergence of Schumpeterian economics in the first part of the 20th century the theories of industrial concentration increased their scope by adding the aspect of technology. Swedish economic historian Erik Dahmén’s theory of "industrial development blocks", from 1950, provides an example of this approach, focusing less on restricted geographical space and more on the economic and technological interrelatedness between entrepreneurs and firms, even within larger communities and across different branches of industry. The theoretical development from Marshall’s pioneering theory until today is finally demonstrated by presenting the newest and most popular theory about industrial concentration: Michael E. Porter’s work on industrial "clusters". The popularity of Porter’s theory, the article states, is to a great extent caused by its wide scope - combining key elements of the theories of Marshall and Dahmén with elements from newer, agency-based theories, especially the transaction cost economics of Oliver E. Williamson. The introduction of agency-based theories, such as Williamson’s "new institutional economics" and the "economic sociology" of Mark Granovetter, have gradually shifted the emphasis from viewing economic institutions as an exogenous force, determining the development of the regions, to a predominantly endogenous approach by which the economic and social advantages obtained in the particular localities are explained as the outcome of actual - albeit theoretically conceived - relations between economic (and social) agents, operating under conditions of bounded rationality or trust. The article concludes that despite the different outline and interpretation of human conduct in these new theories, their development and the scholarly discussion very well illustrate the fundamental relevance and unity of even the older, chronologically and contextually widespread theories of industrial agglomeration, ranging from Marshall via Dahmén to Porter. However, in the future, the real challenge lies in gaining valid empirical evidence in order to test the existing, largely theoretical framework.